Contribution to the improvement of cotton seed storage at the new textile and cotton industrial company (SN-CITEC) in Bobo-Dioulasso in Burkina Faso - Kiessoun Konaté; Dominique Ouryagala Sanou; Balamoussa Santara; Mamoudou Hama Dicko (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
The oil produced by SN-Citec is a vegetable oil made from cotton seeds. The cotton seeds from the cotton plant go through several stages or workshops to give the oil. To obtain a quality oil, it is necessary to control the physico-chemical parameters such as humidity, water content, acidity level, fat content during the storage of the raw material which is cotton. The objective of our study was to contribute to the improvement of the storage of the raw material at SN-Citec: cotton seed. We determined the physico-chemical parameters of four (4) batches of seed after storage. The values obtained were compared to the standards of the codex stand. Thus standard methods were used to evaluate the quality of storage. The results of the analyses of the parameters during storage varied from 4.84% to 5.80% for the water content, 4.77% to 4.94% for the moisture content, 2.53% to 3.65% for the acidity content and 20.28% to 20.45% for the oil content of the seed. All the results found were in accordance with codex standards and the values in the laboratory's archives. This study showed that the oil from SN-Citec is of good quality so to obtain an oil of hygienic and nutritional quality a good method of conservation of the raw material, a check of the moisture content of the seed before and during storage, a reserved environment and a good internal temperature of the materials during storage are important.